1995
DOI: 10.1182/blood.v86.7.2481.2481
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunctions in circulating T lymphocytes from human immunodeficiency virus-1 carriers [see comments]

Abstract: In several models of lymphocyte apoptosis, two alterations of mitochondrial function precede advanced DNA fragmentation: (1) a reduction of mitochondrial transmembrane potential (delta psi m) and (2) an increase in mitochondrial generation of superoxide anion. Here we show that two fluorochromes allow for the identification of analogous mitochondrial perturbations in circulating T lymphocytes from human immunodeficiency virus (HIV)-1+ donors. The first among these fluorochromes, the cationic lipophilic dye DiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(58 citation statements)
references
References 32 publications
5
50
0
3
Order By: Relevance
“…We have extended these findings by looking at various intracellular events leading to HIV Env-induced apoptosis. We observe that the apoptosis in our model was mediated via a mitochondrial pathway, as has been seen by others in Env cocultures [49] and virus infection [18]. We also find that the cells undergoing apoptosis show signs of high ROS, a marker of oxidative stress, and a phenomenon reported in HIV-infected cultures [16] or in lymphocytes from infected patients ex vivo [20].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have extended these findings by looking at various intracellular events leading to HIV Env-induced apoptosis. We observe that the apoptosis in our model was mediated via a mitochondrial pathway, as has been seen by others in Env cocultures [49] and virus infection [18]. We also find that the cells undergoing apoptosis show signs of high ROS, a marker of oxidative stress, and a phenomenon reported in HIV-infected cultures [16] or in lymphocytes from infected patients ex vivo [20].…”
Section: Discussionsupporting
confidence: 86%
“…Apoptosis mediated via various stimuli involves mitochondrial depolarization and ROS production as early events in the apoptotic pathway. In HIV infection, mitochondrial dysfunction has been associated with T cell loss in vivo [18]. To determine the signaling mechanism involved in HIV Envinduced apoptosis, we first determined whether apoptosis was mediated via the mitochondrial pathway.…”
Section: Hiv Env-mediated Apoptosis Involves Mitochondrial Depolarizamentioning
confidence: 99%
See 1 more Smart Citation
“…These findings did not give further clues to the mechanism of increased annexin V staining of B cells, but suggested that this increased staining was not a result of apoptosis. Although we cannot conclude that this abnormal PS exposure on B cells is specific to HAM/TSP, it has been reported that in HIV infection there is not a high level of annexin V positivity, although there are significant levels of mitochondrial depolarization in fresh PBMC [14].…”
Section: Discussionmentioning
confidence: 58%
“…NADPH is formed in cytosol and mitochondria via the hexose monophosphate shunt. Interestingly, seropositive subjects have been shown to have mitochondrial dysfunctions [8], which could contribute to low NADPH levels and GSH reductase activity and lowered GSH/ increased GSSG levels.…”
Section: Functions Of Gshmentioning
confidence: 99%